Levels of homocysteine are increased in metabolic syndrome patients but are not associated with an increased cardiovascular risk, in contrast to patients without the metabolic syndrome - Hajer, Gideon R; van der Graaf, Yolanda; Olijhoek, Jobien K; Verhaar, Marianne C; Visseren, Frank L J (Heart (British Cardiac Society), 2007)
Aim: The metabolic syndrome is associated with increased cardiovascular risk. Elevated plasma homocysteine may cause or result from insulin resistance, and may indicate vascular risk or be actively involved in atherogenesis. The aim of the study was to investigate the relationship between homocysteine, the metabolic syndrome and the incidence of cardiovascular events in patients with manifest vascular disease. Methods: A cohort of 2169 patients with manifest vascular disease was followed for a mean period of 2.8 years. Plasma homocysteine was measured at baseline. Metabolic syndrome was defined by NCEP criteria. Results: Homocysteine levels were higher in metabolic syndrome patients compared to patients without the metabolic syndrome (14.9±0.2 v 14.1±0.2 μmol/l; p = 0.002) and increased with the presence of its components (from 0 to 5) (12.7 to 15.9 μmol/l; p<0.001). During follow-up, 52 strokes, 67 myocardial infarctions, 5 fatal ruptures of aortic aneurysms and 53 vascular deaths occurred. Patients without the metabolic syndrome and homocysteine levels in the highest tertile had increased risk for events (HR 1.9; 95% CI 1.0 to 3.5) compared to patients without the metabolic syndrome and homocysteine levels in the lowest tertile. The presence of the metabolic syndrome increased the risk (HR 2.2; 95% CI 1.2 to 4.2), but elevated homocysteine levels further increased the risk only marginally (2.5; 95% CI 1.4 to 4.6). Conclusions: Metabolic syndrome patients have elevated homocysteine levels, but these higher levels are not associated with an increased risk for new cardiovascular events. In contrast, elevated homocysteine levels confer increased risk in patients without the metabolic syndrome.